2016
DOI: 10.1080/00028487.2016.1238409
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Olfactory Imprinting by Sockeye Salmon at Embryonic and Smolt Stages

Abstract: Anadromous salmonids have an extraordinary ability to migrate back to their natal streams to spawn as adults, but the mechanisms underlying this ability are not completely known. Many experiments indicate that salmon imprint on natal odors at the smolt stage prior to seaward migration, but the life history and population genetics of some species, notably Sockeye Salmon Oncorhynchus nerka, suggest that imprinting also occurs during the period between hatching and emergence from the gravel as fry. To test the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…Havey et al. () found that Sockeye Salmon imprinted to odors at both the alevin and smolt stages in laboratory conditions, and our work showed that fry released in the Cedar River imprinted at the initiation of downstream migration.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Havey et al. () found that Sockeye Salmon imprinted to odors at both the alevin and smolt stages in laboratory conditions, and our work showed that fry released in the Cedar River imprinted at the initiation of downstream migration.…”
Section: Discussionsupporting
confidence: 70%
“…Experimental work has provided evidence of olfactory imprinting by fry (Havey et al. ), but the extent to which they express this ability in natural systems is unclear.…”
mentioning
confidence: 99%
“…Havey et al. () and Quinn et al. () found that imprinting begins during early rearing stages; therefore, constructing hatcheries upstream of release areas may result in unanticipated upstream movement by returning adults.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the stimulation of guanylyl cyclase activity by PEA was significantly greater in olfactory cilia isolated from PEA-imprinted fish than in PEAnaïve fish at the time of the homing migration, which occurred 2 years after exposure to PEA (Dittman et al, 1997). Havey et al (2017) presented experimental evidence for olfactory imprinting to a mixture of odorants containing amino acids and PEA in O. nerka at the embryonic and smolt stages. However, there have been few attempts to identify the properties of natal-stream odours in salmonid populations of the eastern Pacific Ocean.…”
Section: Neurophysiological Studies On Olfactionmentioning
confidence: 81%
“…Havey et al . () presented experimental evidence for olfactory imprinting to a mixture of odorants containing amino acids and PEA in O. nerka at the embryonic and smolt stages. However, there have been few attempts to identify the properties of natal‐stream odours in salmonid populations of the eastern Pacific Ocean.…”
Section: Neurophysiological Studies On Olfactionmentioning
confidence: 99%